U duhu Hamleta: još jedanput o engleskom korpusu u Marinkovićevu Kiklopu - Jukić, Tatjana (2004)
Ranko Marinković's recurrent references to Shakespeare and Homer in Cyclops, his acclaimed 1965 novel organized around his earlier fiction, have from the time of its publication set the tone of its reception. Given Marinković’ s early parody of Joyce’ s Ulysses, largely ignored by the critics, my contribution aims to reassess the genealogy of Marinković’ s narrative interests in Shakespeare and in Joyce, and to thus reposition the complex figuration of genealogy and of fathers and sons, as a formative feature of Cyclops.
ISBN 953-163-235-9
Projekt MZOS
HRV